Planar Lebesgue Measure of Exceptional Set in Approximation of Subharmonic Functions - Girnyk, Markiyan (Журнал математичної фізики, аналізу, геометрії, 2009)
We consider the pointwise approximation of a subharmonic functionhaving finite order by the logarithm of the modulus of an function up to abounded quantity. We prove an estimate from below of the planar Lebesguemeasure of the exceptional Set in such approximation. Mathematics Subject Classification: 31C05, 30E10